Knowledge and attitudes as predictors of cervical cancer screening among women in a Venezuelan urban area. - Núñez Troconis, José; Tulliani, Elisabetta; Martínez, María Gabriela; Fernández, Ninorka (Investigación Clínica, 2013)
The purpose of this research was to investigate how the knowledge and attitudes have influence in Cervical Cancer (CC) screening among Venezuelan women, by realizing a cross-sectional descriptive study based on a structured non disguised questionnaire with closed ended questions: yes/no questions and multiple choices. The survey was performed on 691 volunteers, of which 595 were analyzed. Each patient was asked to fill in the questionnaire. Four hundred ninety three of 522 (94.4%) answered that they knew that Pap smear is for screening CC. Knowledge of Pap smear was statistically significant when it was compared to high educational level (p < 0.0001) al- though 185 (76%) of 244 low educational level interviewees answered that they had the knowledge that the Pap smear is used for screening of CC. Four hundred four of 504 (84.7%; p < 0.001) mentioned that they had a Pap smear at least once. One hundred ninety two (38.1%) of 504 women were adherent to an annual Pap smear test and more than half of the women (n= 337, 67%) had the last Pap smear in the last 1-3 years. Women with a high educational level showed higher adherence to the annual Pap smear screening (68.2%). Two hundred fifty seven (87.4%) of 294 said that they remembered when they got the information about Pap smear. The conclusions of this investigation were that our women were aware about Pap smear, had a good attitude to have a Pap smear and to be adherent to a regularly performed screening.